Basic concepts and curriculum theory in education - Indah Rizki Ramadani; Firman Firman; Riska Ahmad (SCHOULID: Indonesian Journal of School Counseling, 2021)
The curriculum has a domain in education that is contained in various substances, namely: curriculum as part of the field of study, curriculum as a substance in the teaching plan, and curriculum as part of a system. The curriculum functions in shaping and developing cognitive, affective and psychomotor aspects of humans by achieving the vision, mission and goals of national education. The curriculum as a tool can be realized in the form of programs, namely learning activities and experiences that must be carried out by teachers and students in the learning process. This research is a research with a literature study approach that looks at how the nature and description of a dynamic and flexible curriculum and always experiences shifts and changes following the direction and goals of education, which every year the curriculum is continuously updated so as not to be left behind by the times, making the curriculum easily implemented. in every educational institution. The purpose of the curriculum is to produce the best graduates who are knowledgeable, have character, uphold the values of cultural, moral, national norms and have a high level of religiosity.